Nutritional status, sugar sweetened beverage consumption and physical activity level in male and female college students living in dormitory - Wicaksari, Sifa Aulia; Chandra, Dian Novita; Khusun, Helda; Sunardi, Diana (Journal of Community Empowerment for Health, 2024)
Introduction: The global prevalence of obesity is on the rise, including in Indonesia. High energy intake from sugar is a growing concern worldwide due to its association with weight gain, tooth decay, and non-communicable diseases. A prior study revealed that 10.9% of Indonesian adults consumed energy from sweetened beverages in excess of the WHO recommendation. This study aimed to assess the consumption of sweetened beverages in male and female college students in Indonesia. Method: The study was conducted at Universitas Indonesia and involved 107 subjects aged 19-21 years who resided in student dormitories. Result: The result found the median BMI in female was higher than male. In female, 3 out of 10 students was overweight-obese, while 1 out of 10 in male. Interestingly, the median daily intake of sweetened beverages significantly higher in male than female; 387 (25–1580) vs 246 (0–762) ml/day (p=0.001). Added sugar content in beverages in males was higher than half of Indonesian recommendation (28.4 [1.9–134.4] vs 19.2 [0–61.1]) which contributed to energy as much as 170.9 (12.4–625.7) kcal/ day or about 8.9% of total energy intake than female (108.5 [0–394.4] kcal/day). Compared to Indonesian guideline, 12% of male subjects consumed added sugar higher than 50 g/day. Simultaneously, 7 out of 10 subjects consumed energy from sweetened beverages higher than 10% of their total energy intake (WHO recommendation). The BMI and prevalence of overweight-obese were higher in female, while the sweetened beverage was higher in male. It might be caused by the physical activity in male was higher than female. Although male had higher energy intake from SSB, their energy output through physical activity balanced with energy input. Conclusion: These finding alerted the university as educational institution should take an action to prevent this issue since the prevalence of overweight-obesity and sweetened beverage consumption has occurred in young age.